A review on the plant secondary metabolites with special context with North East India - Devi Ritismita; Manash Pratim Sarma (Institute of Advanced Engineering and Science, 2021)
Extracting phytochemicals or phytocompounds for the upliftment of general health and sustainability is one of the greatest needs of the millennium. Plants have immense quality in regard to secondary metabolites although not required for general growth and development yet are very much necessary for forming a protective gear and maintaining homeostasis. With their immense diversity in curing various diseases, these plants' secondary metabolites therefore must be put forth and given much importance in generation and production from the root level to the mission worldwide. Along with the increasing cases of failure in the usage of chemotherapeutic drugs and their utilities, the implementation of secondary metabolites for their various medicinal characteristic in therapeutic cases are also increasing in demand. With the increasing demand for Ayurveda treatment and the popularity of the mass, it can be positively taken up as a means of earning capital and making self-sustaining. North-Eastern states of India in this regard are a vital source of income and also a media to generate and bring indigenous products to the world.